2017
DOI: 10.1021/acsomega.7b00145
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methyl methacrylate) as an Environmentally Responsive Capping Material for Aluminum Nanoparticles

Abstract: We present an investigation of the photochemistry of aluminum nanoparticles (Al NPs) capped with poly(methyl methacrylate) (PMMA). Powder X-ray diffraction and Fourier transform infrared spectroscopy with total attenuated reflection confirm the presence of crystalline aluminum cores and the PMMA cap and allow us to confirm the latter’s photodegradation upon exposure to UV light. The PMMA-Al NPs were also characterized by differential scanning calorimetry coupled with thermogravimetric analysis to study the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
(103 reference statements)
1
6
0
Order By: Relevance
“…The study showed no change in the intensity and width of the peaks corresponding to the pure aluminium in the XRD patterns, and there was no signature for the reflections of aluminium oxide. In comparison with previous studied (Table 2) on polymer-coated (PVA, PVP and PMMA) Al nanoparticles 11,13,15 or organic capping agents such as perfluoroalkyl carboxylic acids, oleic acid, epoxyhexane and epoxydodecane, [16][17][18][19][20] our dual-function surfactant established significant air stability for ah-Al that extended beyond 120 days. These findings indicate that the surfactant-stabilized ah-Al is stable for up to four months.…”
Section: Oxidative and Thermal Stability Of Aluminium Nanoparticlesmentioning
confidence: 62%
See 2 more Smart Citations
“…The study showed no change in the intensity and width of the peaks corresponding to the pure aluminium in the XRD patterns, and there was no signature for the reflections of aluminium oxide. In comparison with previous studied (Table 2) on polymer-coated (PVA, PVP and PMMA) Al nanoparticles 11,13,15 or organic capping agents such as perfluoroalkyl carboxylic acids, oleic acid, epoxyhexane and epoxydodecane, [16][17][18][19][20] our dual-function surfactant established significant air stability for ah-Al that extended beyond 120 days. These findings indicate that the surfactant-stabilized ah-Al is stable for up to four months.…”
Section: Oxidative and Thermal Stability Of Aluminium Nanoparticlesmentioning
confidence: 62%
“…Reducing or avoiding the self-oxidation of highly reactive metals (such as Al, Zr and Mg) and decreasing the agglomeration of nanoparticles are the principal problems to be addressed for research into energetic materials to obtain nanoparticles with improved physical and chemical properties. [12][13][14][15][16][17][18][19][20][21] By nature, Al has more affinity towards oxygen. Therefore, preventing oxide formation on the surface of the aluminium nanoparticles is a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second synthetic approach is the catalytic decomposition of alanes. Within this approach amine alanes such as H 3 AlNMe 2 Et [11,[16][17][18], H 3 AlNMe 3 [19], H 3 AlNEt 3 [20], H 3 AlN(C 4 H 8 )(CH 3 ) [17] or H 3 AlNMePyr [21] are decomposed using Ti(OiPr) 4 [11,16,17,19] or TiCl 4 [21] as a catalyst. The ether adducts of AlH 3 are known to decompose under similar conditions [22], their use in the wet chemical synthesis of Al nanoparticles is however much more uncommon compared to their amine counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled oxidation can be avoided applying various passivating agents such as oleic acid [18,23,28], perfluorated carboxylic acids [19,21,29], phosphines [12], amines [30], or thin transition metal coatings [20]. Also, polymers like PVP [31], PMMA [16], and polyepoxides [32,33] can be used to protect the surface.…”
Section: Introductionmentioning
confidence: 99%